Brain Cell Biology - Augustine, George J.; SpringerLink (Online service) (New York : Springer US : Imprint: .)
Brain Cell Biology publishes original contributions dealing with the structure and function of the nervous system. Our focus is on studies that employ contemporary experimental approaches, such as live-cell imaging and molecular biological manipulations of neural genes, to advance our understanding of basic mechanisms of neuronal and glial cell biology, synaptic transmission, cell motility, intracellular trafficking, neural signaling and neurological disorders. Topics covered include Synaptic signaling Neuron-glial interactions Membrane trafficking Regulation of protein synthesis Signal transduction Ion channels and electrical signaling Dendritic integration Sensory transduction Molecular neurobiology Neurocytology Neural development.
Keywords: Neurosciences; Life sciences; Cell biology; Developmental biology; Neurobiology; Microscopy; Neurosciences; Neurobiology; Cell Biology; Life Sciences, general; Biological Microscopy; Developmental Biology